Development of specialized hand-held electronic dictionaries with special reference to those for medical professionals and students - Yamada, Shigeru (Penerbit Universiti Kebangsaan Malaysia, 2019)
In the course of 25 years of their existence, hand-held electronic dictionaries (HHEDs) have become more comprehensive in terms of content and more sophisticated technologically. One dimension in which the specification of these devices has advanced is the subject field of HHEDs. Medicine is one prime example of this trend. Medical HHEDs, which include many specialized, not readily accessible print dictionaries, save the user considerable time and effort. The HHED’s electronically enhanced navigability makes almost redundant the rules and conventions associated with consultation of print dictionaries. The market of medical HHEDs has been dominated by Casio and Seiko Instruments Inc. (SII). Each manufacturer contracted a block of publishers to supply contents for its respective set of products. With SII’s withdrawal from the HHED business, Stedman’s Medical Dictionary and its Japanese version were included in Casio’s HHED. The integration of a source dictionary and its translated version to be exploited for bi-directional consultation and learning in either language can be a useful, potential avenue for the next generation of HHEDs, in the environment rendered more competitive by a wide array of smart devices with Internet connectivity.